Risk Perception and Ethnic Background in Construction Workers: Results of a Cross-Sectional Study in A Group of Trainees of a Vocational School in Italy - Federico Ricci (European Journal of Investigation in Health, Psychology and Education, 2021)
Risk perception can be influenced by cultural background. The study aims to evaluate risk perception, considering different ethnicities of construction workers from vocational schools in Italy. We administered a questionnaire investigating four different dimensions: Perceived behavioral control (PBC), Danger perception (DP), Safety climate (SC), and Attitude towards safe actions (ATSA). 562 workers answered: 72.4% from Italy, 14.2% from eastern Europe, 9.4% from Balkans, and 3.9% from North Africa. The participants indicated quite low control, attributable to the haste in performing the job. The workers perceived their specific job tasks as riskier compared to the tasks of their colleagues. They reported as fundamental the respecting of safety rules, but indicating that supervisors do not adequately promote safety behaviors. Finally, construction workers judged as “brave” the colleagues working without protective equipment. When compared to Italians, North Africa workers showed a lower perception of the possibility to control their safe behaviors (p=0.040), while both eastern Europeans and Balkan obtained higher scores at the ATSA dimension, indicating a kind of fatalistic acceptance of the risky situations at work. Eastern Europeans also showed a lower perception of the dangers (p=0.002), while Balkan demonstrated a perception of SC even better than the Italian group (p=0.005).